The Isolation of DNA by Polycharged Magnetic Particles: An Analysis of the Interaction by Zeta Potential and Particle Size - Haddad, Yazan; Xhaxhiu, Kledi; Kopel, Pavel; Hynek, David; Zitka, Ondrej; Adam, Vojtech (International journal of molecular sciences, 2016)
Magnetic isolation of biological targets is in major demand in the biotechnology industry today. This study considers the interaction of four surface-modified magnetic micro- and nanoparticles with selected DNA fragments. Different surface modifications of nanomaghemite precursors were investigated: MAN37 (silica-coated), MAN127 (polyvinylpyrrolidone-coated), MAN158 (phosphate-coated), and MAN164 (tripolyphosphate-coated). All particles were positive polycharged agglomerated monodispersed systems. Mean particle sizes were 0.48, 2.97, 2.93, and 3.67 μm for MAN37, MAN127, MAN164, and MAN158, respectively. DNA fragments exhibited negative zeta potential of -0.22 mV under binding conditions (high ionic strength, low pH, and dehydration). A decrease in zeta potential of particles upon exposure to DNA was observed with exception of MAN158 particles. The measured particle size of MAN164 particles increased by nearly twofold upon exposure to DNA. Quantitative PCR isolation of DNA with a high retrieval rate was observed by magnetic particles MAN127 and MAN164. Interaction between polycharged magnetic particles and DNA is mediated by various binding mechanisms such as hydrophobic and electrostatic interactions. Future development of DNA isolation technology requires an understanding of the physical and biochemical conditions of this process.
Keywords: magnetic; Nanoparticles; nanoparticles; magnetismus; biotechnologie; Real-Time Polymerase Chain Reaction; particle size; DNA; mikroskopie elektronová rastrovací; velikost částic; DNA isolation; zeta potential; Biotechnology; Magnetics; kvantitativní polymerázová řetězová reakce; Microscopy, Electron, Scanning; nanočástice; Particle Size